Diagnostic accuracy of clinical stroke scores for distinguishing stroke subtypes: A systematic review - Mwita, C; Kajia, D; Gwer, S; Mwita, C; Gwer, S; Etyang, A; Newton, C; Newton, C; Newton, C (Joanna Briggs Institute, 2012)
Review question/objective This review aims to examine the sensitivity and specificity of clinical stroke scores in distinguishing ischemic and hemorrhagic stroke subtypes in patients with acute stroke and determine the score best suited for use in resource poor settings. The specific review question is: what is the sensitivity and specificity of clinical stroke scores in distinguishing ischemic from hemorrhagic stroke in patients with acute stroke, compared with non-contrast computed tomography?